Breadcrumbing in Romantic Relationships: A Conceptual and Theoretical Analysis - Tochkov, Karin (Advances in Social Sciences Research Journal, 2025)
Breadcrumbing is an increasingly recognized yet underexplored phenomenon in romantic relationships, particularly within digital dating contexts. Defined as the act of sending intermittent signals of interest without genuine intention to pursue a committed relationship, breadcrumbing overlaps conceptually with ghosting, orbiting, and other ambiguous relational behaviors. This article develops a theoretical and conceptual framework for understanding breadcrumbing in romantic relationships. Drawing on attachment theory, social exchange theory, and reinforcement principles, it explores the motives of breadcrumbers, the vulnerabilities of recipients, and the persistence of breadcrumbing dynamics. The article also situates breadcrumbing within a broader taxonomy of digitally mediated relational practices, examining its ethical implications, technological affordances, and potential consequences for individual well-being and cultural norms. Clinical considerations and directions for future research are provided.